2009
DOI: 10.1027/1614-0001.30.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relations Among Executive Functions, Fluid Intelligence, and Personality

Abstract: Executive functions (EFs) are important for goal-directed behavior and have been linked with a number of important constructs like intelligence. The current study examined the link between EFs and aspects of normal and abnormal personality. Latent variables of working memory, fluency, response inhibition, and vigilance EFs were examined along with fluid intelligence (gF). It was found that the EFs were separate yet correlated, and that each was related to gF. Furthermore, it was found that aspects of personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
91
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 26 publications
11
91
1
3
Order By: Relevance
“…In particular, findings from other research (e.g. Murdock et al, 2013;Unsworth et al, 2009) were not replicated.…”
Section: Personality and Executive Functionmentioning
confidence: 64%
See 3 more Smart Citations
“…In particular, findings from other research (e.g. Murdock et al, 2013;Unsworth et al, 2009) were not replicated.…”
Section: Personality and Executive Functionmentioning
confidence: 64%
“…However, it did not correlate with either of these variables in Study 3. Unsworth et al (2009) found a link between Openness to Experience and Fluency. Murdock et al (2013) reported that Openness was associated with both cognitive flexibility and updating / monitoring (which in their implementation was based on similar fluency tasks to the cognitive flexibility variable in the current Study 3).…”
Section: Personality and Executive Functionmentioning
confidence: 92%
See 2 more Smart Citations
“…Anderson et al, 1999;Damasio & Anderson, 1993;Hebb, 1939Hebb, , 1945Hebb & Penfield, 1940, Dрема Пурић, 2013) и осоJинама личносLи (нDр. Dolan & Anderson, 2002;Knežević, Savić, Špirić, Vermetten, & Vidaković, 2011;Logan et al, 1997;Luu, Colins, & Tucker, 2000;Morgan & Lilienfeld, 2000;Purić & Pavlović, 2011;Unsworth et al, 2010;Dрема Пурић, 2013). Ка9а DосмаLрамо о9нос инLели:енције и е:зекуLивних функција, нека исLраживања указују на DосLојање DовезаносLи између функције ажурирања и флуи9не и крисLализоване инLе-ли:енције (нDr.…”
Section: уводunclassified